New species and new distributional records of Neotropical Mantispidae (Insecta: Neuroptera) - Ardila-Camacho, Adrian; Calle-Tobón, Arley; Wolff, Marta; Stange, Lionel A. (Zootaxa, 2018)
The Neotropical fauna of Mantispidae is currently composed of 106 species. We provide new distributional records of Mantispidae from Colombia and Panama. Three new species are described, one in Symphrasinae from Colombia, and two in Mantispinae from Colombia and Panama. Haematomantispa nubeculosa (Navás, 1933) and Leptomantispa axillaris (Navás, 1908) are reported from Colombia for the first time, the former being the first record of the genus in the country. New locality records for other species previously known from Colombia are also given. For Panama, we report Anchieta fasciatella (Westwood, 1867) and Trichoscelia iridella (Westwood, 1867) for the first time, the former is herein newly transferred from Plega to Anchieta. Three names Mantispa confluens Navás, 1914, n. syn., Buyda apicata Navás, 1926, n. syn., and Mantispa neotropica Navás, 1933, n. syn., are here synonymized with Buyda phthisica (Gerstaecker, 1885). Updated keys for the genera of Mantispinae, and species of genera Trichoscelia, Buyda, and Climaciella from Colombia are included. With this new information, the known species richness of Mantispidae from Colombia increases from 21 to 26, and from 16 to 19 species in Panama.